'What sholde I make a lenger tale of this?': Linguistic and stylistic analysis of rhetorical questions in the Canterbury Tales - Maiz Arévalo, Carmen (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen